Horse and donkey parasitology: differences and analogies for a correct diagnostic and management of major helminth infections - Francesco Buono; Vincenzo Veneziano; Fabrizia Veronesi; Marcelo Beltrão Molento; Rudi Cassini; Laura Rinaldi (Parasitology, 2023)
In June 2022, at the XXXII Conference of the Italian Society of Parasitology, the parallels of the main endoparasitic infections of horses and donkeys were discussed. Although these 2 species are genetically different, they can be challenged by a similar range of parasites (i.e. small and large strongyles, and Parascaris spp.). Although equids can demonstrate some level of resilience to parasites, they have quite distinct helminth biodiversity, distribution and intensity among different geographical locations and breeds. Heavily infected donkeys may show fewer clinical signs than horses. Although parasite control is primarily provided to horses, we consider that there may be a risk of drug-resistance parasitic infection through passive infection in donkeys when sharing the same pasture areas. Knowing the possible lack of drug efficacy (<90 or 80%), it is advocated the use of selective treatment for both species based on fecal egg counts. Adult horses should receive treatment when the threshold exceeds 200–500 eggs per gram (EPG) of small strongyles. Moreover, considering that there are no precise indications in donkeys, a value >300 EPG may be a safe recommendation. We have highlighted the main points of the discussion including the dynamics of helminth infections between the 2 species.